2022
DOI: 10.1158/1078-0432.ccr-22-0404
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Serum Autoantibody Signatures Predict Recurrence and Toxicity in Melanoma Patients Receiving Adjuvant Immune Checkpoint Blockade

Abstract: Purpose: Adjuvant immunotherapy produces durable benefit for patients with resected melanoma, but many develop recurrence and/or immune-related adverse events (irAE). We investigated whether baseline serum autoantibody (autoAb) signatures predicted recurrence and severe toxicity in patients treated with adjuvant nivolumab, ipilimumab, or ipilimumab plus nivolumab. Experimental Design: This study included 950 patients: 565 fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…This ampli cation facilitates their measurement. In general support of the utility of antibodies as biomarkers, a very recent study showed that antibodies against self-antigens can serve as biomarkers of melanoma recurrence following adjuvant therapy (52). The antibody biomarkers against non-self antigens described here are additionally unique measurements of patient status.…”
Section: Discussionsupporting
confidence: 52%
“…This ampli cation facilitates their measurement. In general support of the utility of antibodies as biomarkers, a very recent study showed that antibodies against self-antigens can serve as biomarkers of melanoma recurrence following adjuvant therapy (52). The antibody biomarkers against non-self antigens described here are additionally unique measurements of patient status.…”
Section: Discussionsupporting
confidence: 52%
“…This underscores that autoantibodies are likely at stake in some irAEs, including those affecting the thyroid gland [45]. Recent work by Johannet et al showed that baseline serum autoantibody signatures are predictive of severe irAEs (not limited to thyroiditis) with adjuvant anti-PD-1 and/or anti-CTLA-4 [46], which presents further evidence that preexistent subclinical autoimmunity may be at the root of various irAEs. Importantly, CXCL13 increase does not per se indicate TLS formation, as tumor-reactive T cells identified through CXCL13 expression can also be a source that expands upon treatment in ICI-responders [47].…”
Section: Discussionmentioning
confidence: 95%
“…No association was found between median baseline autoantibody levels and disease recurrence in a prospective study of melanoma patients treated with ICB in the adjuvant setting, although an autoantibody signature that predicted recurrence-free survival and irAE development with high accuracy was reported. 37 The authors posited that the immunogenicity of specific autoantigens, such as those included in their recurrence signature, may possess superior predictive power relative to total autoantibody levels. 37 Lack of relationship between pretreatment and post-ICB autoantibody levels and clinical endpoints has also been described in a pan-cancer study, 38 although the authors assayed presence of a prescribed and limited panel of autoantigens and they did not examine autoantibody boostability relative to response.…”
Section: Discussionmentioning
confidence: 99%
“…37 The authors posited that the immunogenicity of specific autoantigens, such as those included in their recurrence signature, may possess superior predictive power relative to total autoantibody levels. 37 Lack of relationship between pretreatment and post-ICB autoantibody levels and clinical endpoints has also been described in a pan-cancer study, 38 although the authors assayed presence of a prescribed and limited panel of autoantigens and they did not examine autoantibody boostability relative to response. With regard to chemotherapy associations with autoantibodies, a reduction of autoantibody levels was observed in a breast cancer study after treatment with different combinations of chemotherapy, radiation, and hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%